Challenges And Solutions of Healthcare Workers In Providing Social Security Administering Body (BPJS) Patient Services In The Digital Era at Royal Prima Marelan Hospital - Sri Lestari Ramadhani Nasution; Monisa Olivia Zulri; May Raflin Br.Sinaga; Ermi Girsang (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Indonesia’s national health insurance program,  administered by the Social Security Administering Body for Health (BPJS Kesehatan),  faces mounting  challenges in the digital era, including rising workloads, system disruptions, and limited dissemination of policy updates. At Royal Prima Marelan Hospital, these issues affect service efficiency and patient satisfaction. This study examines the challenges and adaptive strategies of healthcare workers in delivering BPJS services within a digital healthcare environment. A qualitative case study was conducted at Royal Prima Marelan Hospital, Medan, from January to November 2025. Participants included nine purposively selected informants, six primary healthcare workers, and three triangulation informants from hospital management and administrative units. Data were collected through observation, in-depth interviews, and document review, and analyzed descriptively using data reduction, data display, and conclusion drawing.  Despite the use of digital systems such as  VClaim, INA-CBGs, and SIMRS, healthcare workers encountered persistent barriers, including unstable internet connections, limited infrastructure, and insufficient digital skills. These challenges increase administrative workload, delay services, reduce efficiency, and lower staff motivation. Adaptive responses included internal digital training, manual backup documentation, and gradual improvements to systems and networks. Digital transformation has not fully alleviated workload pressures due to infrastructural and competency gaps. Strengthening digital infrastructure, enhancing interoperability, and providing continuous digital training are essential for sustainable BPJS service delivery. Future research should explore innovations such as AI-based claim management and automated audit systems.Keywords: Challenges, Healthcare Worker Adaptation, BPJS Kesehatan Services, Digital Transformation.